2021
DOI: 10.1021/acs.jafc.1c04777
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Small Subunits of Laccase (ssPOXA3a/b) in Laccase Production by Pleurotus eryngii var. ferulae

Abstract: The small subunit, ssPOXA3a/b, and the large subunit, POXA3, are indispensable components of typical heterodimeric laccase (Lacc2) in white rot fungi. However, the enzymatic and biological functions of ssPOXA3a/b remain unclear. The present study revealed that neither ssPOXA3a nor ssPOXA3b per se has a catalytic ability, whereas their combination with POXA3 (and especially ssPOXA3b) enhances the activity, thermostability, and pH stability of POXA3. In Pleurotus eryngii var. ferulae, there was no regulatory rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…More recently, an equivalent heterodimeric complex was identified and characterized in P. eryngii var. ferulae (Zhang et al, 2021) whose laccase-like subunit has been reclassified as a NLAC in this study (see Figure S8). Despite there is no known catalytic activity associated to these small proteins, both studies agreed in the superior thermostability of the heterodimers compared to the monomeric enzymes (Faraco et al, 2008;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, an equivalent heterodimeric complex was identified and characterized in P. eryngii var. ferulae (Zhang et al, 2021) whose laccase-like subunit has been reclassified as a NLAC in this study (see Figure S8). Despite there is no known catalytic activity associated to these small proteins, both studies agreed in the superior thermostability of the heterodimers compared to the monomeric enzymes (Faraco et al, 2008;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ferulae (Zhang et al, 2021) whose laccase-like subunit has been reclassified as a NLAC in this study (see Figure S8). Despite there is no known catalytic activity associated to these small proteins, both studies agreed in the superior thermostability of the heterodimers compared to the monomeric enzymes (Faraco et al, 2008;Zhang et al, 2021). The fact that at least one gene of small subunit-like proteins is found in every studied genome encoding NLACs (Ruiz-Dueñas et al, 2021) suggests the formation of heterodimers is a general rule for this type of laccase-like enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that P. eryngii var. ferulae demonstrates excellent laccase production and dye decolorization capabilities during cocultivation [11,24,27]. However, the lack of a genetic transformation system is an obstacle that restricts further molecular studies.…”
Section: Discussionmentioning
confidence: 99%
“…A Biospin Plant Total RNA Extraction Kit (BIOER, Hangzhou, China) was used to extract mycelial RNA from all transformants. cDNA was constructed using HiScript III RT SuperMix for qPCR containing gDNA wiper (Vazyme, Nanjing, China), as described previously [27]. The primers were designed by the primer-blast of the NCBI website (https://www.ncbi.nlm.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…The white-rot basidiomycetes have the ability to produce hydrolytic enzymes that are involved in hydrolyzing cellulose and hemicellulose, as well as ligninolytic enzymes that are involved in degrading lignin during whole fermentation of lignocellulose (Elissetche et al 2007;Birhanli and Yesilada 2013;Thamvithayakorn et al 2019). Similarly, previous studies had indicated that Lentinula edodes and Pleurotus eryngii have the capacity to produce laccase (Yan et al 2019;Liu et al 2020a;Zhang et al 2020Zhang et al , 2021. Furthermore, many studies have shown that different species of fungi have different abilities in producing ligninase (Guo et al 2017;Huang et al 2019;An et al 2021a).…”
Section: Species-dependent Laccase Productionmentioning
confidence: 99%